The effect of Lemongrass (Cymbopogon nardus) Extract in inhibiting Bread Fungal Growth, Aspergilus Oyizae Using a combination of N-Hexane-Ethanol Solvent - Priyo Hartanto; Prapti Sedijani; Lalu Zulkifli; Miko Erniarti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The purpose of this study was to determine the effect of lemongrass extract (Cymbopogon nardus) in inhibiting the growth of the bread fungus Aspergillus oryzae by using a combination of lemongrass extract with n-hexane as a solvent. This type of research is experimental research. The population in this study were all types of mushrooms isolated from bread. The sample used was the fungus Aspergillus oryzae isolated from bread. Lemongrass extraction was carried out by maceration method with n-hexane and ethanol as solvents separately, followed by mixing the two extracts with a combination of n-hexane extract: ethanol extract respectively as follows: 1:1; 2:1 and 1:2 before evaporation. The inhibition test of lemongrass extract against the fungus Aspergillus oryzae was carried out by growing the fungus on PDA media which had been supplemented with lemongrass extract with a concentration of 0.6%; 0.8% and 1%. Data were analyzed using the ANOVA test at a significance level of 95%, followed by the Honest Significant Difference (BNJ) test. The results showed that the combination of n-hexane extract-ethanol extract 1:1 and 1:2 showed low inhibition at all concentrations tested, while the combination 1:2 with 1% lemongrass extract concentration was the best combination in inhibiting the growth of the fungus Aspergillus oryzae ( 1/4 control mycelium colony diameter) and showed 74% inhibitory activity (strong inhibitory category). From the research, it was concluded that lemongrass extract using a combination of ethanol solvents, N-Hexane extract - ethanol extract with a 1:2 combination applied with a concentration of 1% inhibited the growth of the fungus Aspergillus oryzae in the category of strong inhibition, with an inhibitory activity of 74%.